'We Are All in This Together'. Collective Bonuses and Incentives in the United Kingdom and Europe: The Real Performance-Related Pay?. (18th August 2020) - Brown, Duncan
'We are all in this together' has been a common leadership cry during the coronavirus crisis. But do their rewards designs generally reinforce collective performance? Why have collective bonus and incentive plans made little headway in Europe and what is the evidence on their effectiveness? The author presents findings from a bonus and incentive research review carried out for a major oil company. He found two-thirds of companies operate variable pay plans, with three-quarters of them based on individual performance. Collective plans are, however, spreading in incidence. The research literature he found replicates the North American evidence, indicating collective schemes are associated with higher performance across a variety of metrics. But they are not universally successful. Risks include diminishing effectiveness over time and lack of employee understanding. The research highlights success depends on tailoring to suit the culture and using a range of high-performance work practices. The author concludes success is more likely where collective plans are viewed 'not just as a vehicle for disseminating incentives but for imparting a sense of shared ownership'.